2014
DOI: 10.1016/j.jsha.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Severe reversible myocardial injury associated with aluminium phosphide toxicity: A case report and review of literature

Abstract: Aluminium phosphide is commonly used as an insecticide and can be toxic to humans at the cellular level by interfering with mitochondrial energy metabolism. We report on three cases of severe aluminium phosphide cardio-toxicity, resulting in severe decrease in both ventricular heart functions. The first case succumbed to intractable ventricular arrhythmias complicated by multi-organ failure before she died; while the other two cases required invasive hemodynamic support and eventually improved over the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…Bhasin et al demonstrated a similar pattern of global hypokinesia of the left ventricule walls in 80% of their cases. Elabbassi et al had reported normalization of echocardiographic findings in aluminium phosphide poisoning survivors by the fifth day [11]. Concerning our case, the TTE control showed a gradual improvement in the left ventricular ejection fraction by the 14th day.…”
Section: Discussionsupporting
confidence: 52%
“…Bhasin et al demonstrated a similar pattern of global hypokinesia of the left ventricule walls in 80% of their cases. Elabbassi et al had reported normalization of echocardiographic findings in aluminium phosphide poisoning survivors by the fifth day [11]. Concerning our case, the TTE control showed a gradual improvement in the left ventricular ejection fraction by the 14th day.…”
Section: Discussionsupporting
confidence: 52%
“…Despite its neurotoxicity, there is not much evidence for the cardiac toxicity of this metal. Few observations were made with aluminium phosphide (Elabbassi, Chowdhury & Fachtartz ; Mohan et al . ), and aluminium acetylacetonate (Corain et al .…”
Section: Discussionmentioning
confidence: 99%
“…In AF intoxication, the clinic findings are severe vomiting attacks, resistant hypertension, and metabolic acidosis. Through mitochondrial cytochrome C inhibition, it leads to cardiac and pulmonary toxicity [4,9]. Cardiac depression causes resistant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Within short time after the formation of phosphine gas, the death occurs [3]. For humans, the toxic dose is 20 mg/kg, while lethal dose is 50 mg/kg [4]. Most of the deaths, which occur generally due to cardiovascular toxicity, occur within first 12-24 hours [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation